Identifying iNOS and glycogen as biomarkers for degenerated cerebellar purkinje cells in autism spectrum disorder: Protective effects of erythropoietin and zinc sulfate - Abdulaziz M. Al-Garni; Sara A. Hosny; Faris Almasabi; Ayed A. Shati; Norah M. Alzamil; Asmaa M. ShamsEldeen; Asmaa A. El-Shafei; Fahaid Al-Hashem; Hind Zafrah; Amro Maarouf; Bahjat Al-Ani; Ismaeel Bin-Jaliah; et al. (PLoS ONE, 2025)
Autism spectrum disorder (ASD) is a collective neurodevelopmental disorder affecting young children and accounting for 1% of the world’s population. The cerebellum is the major part of the human brain affected by ASD and is associated with a substantial reduction in the number of Purkinje cells. An association between ASD and the expression of the nitrosative stress biomarker inducible nitric oxide synthase (iNOS), as well as glycogen deposition in damaged Purkinje cells, has not been previously reported in the medical literature. To explore this correlation, young rats were injected with propionic acid (PPA) (500 mg/kg) for 5 days (model group), while the protection groups were treated with either erythropoietin (EPO, 5,000 U/kg) or 2 mg/kg zinc sulfate immediately after the PPA injections. ASD-like features were developed in the model group, as evidenced by cerebellum damage (degeneration of Purkinje cells) and cerebellar dysfunction (behavioral impairment). This study documented the exclusive expression of iNOS in the degenerated Purkinje cells, along with glycogen deposition in these cells. Additionally, PPA significantly (p < 0.001) modulated cerebellar tissue levels of mammalian target of rapamycin (mTOR), gamma-aminobutyric acid (GABA), GABAA receptor, serotonin, the marker of neuronal loss (calbindin D28K), and social interaction deficit. Some of these parameters were differentially protected by EPO and zinc sulfate, with the former providing greater protection than zinc sulfate. Furthermore, a significant correlation between the iNOS score and these parameters associated with ASD was observed. These findings demonstrate the colocalization of iNOS and glycogen in the damaged Purkinje cells induced by ASD, along with the modulation of ASD parameters, which were protected by EPO and zinc sulfate treatments. Thus, these potential novel biomarkers may offer possible therapeutic targets for the treatment of ASD.